Knowledge, attitude, and willingness toward breast magnetic resonance imaging screening among women at high risk of breast cancer in Beijing, China - Jing Lu; Hongwei Ren; Yuhan Liu; Yuxia Wang; Youzhi Rong; Yahui Wang; Feie Wang; Tianran Li; Liutong Shang (BMC, 2024)
Abstract Background Annual breast magnetic resonance imaging (MRI) is highly recommended to assist mammography for women at high risk of breast cancer (BC). This study explored the knowledge, attitude, and willingness toward breast MRI screening among women at high risk of BC. Methods This cross-sectional study enrolled women at high risk of BC between August 2022 and January 2023 in Beijing, China. A structural equation model (SEM) was used to analyze the relationships among knowledge, attitude, and willingness. Results A total of 596 questionnaires were collected, and 412 questionnaires (69.13%) were valid. The women's knowledge and attitude scores were 7.75 ± 2.79 (possible range: 0-12) and 48.53 ± 6.31 (possible range: 13-65). Among the women, 297 (72.09%) were willing to undergo regular breast MRI screening. The SEM showed that knowledge had direct effect on attitude [β = 0.77, 95% CI: (0.57, 0.98), P < 0.001], the attitude had direct effect on willingness [β = 0.02, 95% CI: (0.01, 0.02), P < 0.001], knowledge had an indirect effect on willingness through attitude [β = 0.01, 95% CI: (0.01,0.02), P < 0.001], and the direct effect of knowledge on practice was not significant. Conclusions The women at high risk of BC had insufficient knowledge and a relatively positive attitude toward breast MRI screening. Most of them were willing to undergo regular breast MRI screening. Advertising and public health education programs should be designed to improve their knowledge and attitude, therefore improving their willingness and practice.